2008
DOI: 10.1080/10826080802241243
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Risk in Research Participation Among Underserved Minority Drug Users

Abstract: Research with underserved minority drug users is essential to quality health care and prevention. Understanding how participants perceive risk in research is necessary to inform research regulators so that research protections are neither lax, exposing participants to harm, nor overly stringent, thereby denying access to beneficial research. Data from 37 semistructured interviews of underserved, African-American crack cocaine users, collected from February to May 2006 in a large, urban setting, were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Compulsive thoughts and impulsive behaviors associated with addiction have often led to more general claims of drug users’ compromised autonomy. While decisional capacity may be impaired during periods of intoxication or cravings, the emphasis on moral agency and personal responsibility expressed by some of our respondents adds to a growing body of ethics scholarship calling for appreciation and cultivation of autonomy in illicit drug using and other vulnerable research populations (Buchanan, 2008; Foddy & Savulescu, 2006; Slomka et al, 2008). …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Compulsive thoughts and impulsive behaviors associated with addiction have often led to more general claims of drug users’ compromised autonomy. While decisional capacity may be impaired during periods of intoxication or cravings, the emphasis on moral agency and personal responsibility expressed by some of our respondents adds to a growing body of ethics scholarship calling for appreciation and cultivation of autonomy in illicit drug using and other vulnerable research populations (Buchanan, 2008; Foddy & Savulescu, 2006; Slomka et al, 2008). …”
Section: Discussionmentioning
confidence: 86%
“…However, as drug use investigators have long noted, such research efforts are stymied by how difficult it is to recruit these “hidden populations” (Ompad et al, 2008; Scott, 2008; Vernon, 2007; Watters & Biernacki, 1989). There is a growing consensus that breaking down recruitment barriers requires an understanding of local beliefs about research practices within the context of community norms (Fisher, 2004; Fry, Madden, Brogan, & Loff, 2006; Grady et al, 2006; Oransky et al, 2009; Plumridge & Chetwynd, 1998; Rhodes et al, 2008; Slomka et al, 2008; Velleman et al,1993). This preliminary investigation adds to the growing literature by highlighting the moral lens through which street drug users view ethical dilemmas encountered by addiction researchers and illuminates new areas meriting investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21] Few investigators have considered the role of study type in examining participation in HIV-related research. Our earlier qualitative research showed that individuals with or at risk for HIV perceived risks and benefits of hypothetical survey, medical, and vaccine studies differently, 22 suggesting that perception of risk-benefit ratio based on type of study could also be a factor in deciding whether to participate in research.…”
Section: Introductionmentioning
confidence: 99%